The Effectiveness of Stimuler Application as Learning Media to Improve Students’ Speaking Skills at Vocational School - Salsa Ayu Denistiani (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2025)
The purpose of this study is to assess the Stimuler application's effectiveness as a learning media for improving vocational school students' speaking skills. The Stimuler application was chosen for its advanced artificial intelligence features that offer real-time feedback and simulate real-world communication, which is critical in vocational education where speaking skills are essential for workplace readiness. The study utilized a quasi- experimental design, with an experimental group using the Stimuler application and a control group using conventional techniques. Both groups were assessed through pre- and post-tests. The research involved 38 participants, with 22 students in the experimental group and 16 in the control group, over a period of four weeks. Researcher calculated that the experimental group's mean post-test score increased by an average of 15.1 points (from 65.4 to 80.5), while the control group showed a minimal increase of 3.9 points (from 64.8 to 68.7). These findings highlight the Stimuler application's ability to improve students' speaking skills through its AI-powered interactive features. The significant improvement in the experimental group suggests that the tool can offer a more effective alternative to traditional teaching methods in vocational education, where communication skills are key to students' future professional success.